Admission policies for Greek Universities: A Historico-sociological View of the Period 1837-2010 - Bouzakis, Siphis (Études helléniques / Hellenic Studies, 2011)
The author of this article examines the significant turning points of the admission policies of Greek universities. In a historical-sociological approach he analyses the factors that lead from the free admission policy of 1837 to the admission requirements in force since 1922. Over the decades that followed, the relationship between the lyceum and the university has become very strained. Moreover, the limited number of students admitted to the universities and technological institutes of higher learning and the strict entrance exams have led to the promotion of tuition fees, student migration and the erosion of the educational mission of the lyceum. There is not much hope for any solution and improvement of the Greece’s educational system in the near future, although debate has started on the admission system of universities and technological institutes of higher learning.